2009
DOI: 10.1016/j.susc.2009.08.022
|View full text |Cite
|
Sign up to set email alerts
|

CO adsorption and dissociation on iron oxide supported Pt particles

Abstract: Abstract. We studied CO adsorption on Pt part icles deposited on well-ordered Fe3O4 (111) thin films grown on Pt(111) by temperature programmed desorption (TPD). A highly stepped Pt(111) surface produced by ion sputter ing and annealing at 600 K was studied for comparison. Structural characterization was performed by scanning tunneling microscopy and Auger electron spectroscopy. The TPD spectra revealed that in addition to the desorption peaks at ~ 400 and ~ 480 K, assigned to CO adsorbed on Pt(111) facets and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 39 publications
3
35
0
2
Order By: Relevance
“…Nucleation and growth of Pt particles on Fe 3 O 4 (111) films have previously been studied in our laboratories by STM and TPD [6,12,13]. 111) and Pt(111) [6].…”
Section: Resultsmentioning
confidence: 99%
“…Nucleation and growth of Pt particles on Fe 3 O 4 (111) films have previously been studied in our laboratories by STM and TPD [6,12,13]. 111) and Pt(111) [6].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the authors have subsequently shown that such an FeO overlayer on Pt can enhance CO oxidation activity [475; 478]. Sun et al [477] found that CO can dissociate on low-coordination sites on supported Pt clusters resulting in a build-up of carbon, and found that Fe from the support diffuses onto (or into) the Pt clusters above 600 K. Platinum is one of several metals investigated to catalyse PEC water splitting at α-Fe 2 O 3 surfaces (e.g. [518][519][520]).…”
Section: Platinummentioning
confidence: 99%
“…One may thus be relatively certain that Pt deposited on Al 2 O 3 or FeO x will form nanodots (i.e., discrete, droplet-like islands on the nanoscale) that remain intact, even in the presence of some surface oxidation of the noble metal or subsequent thermal sintering [23]. On the other hand, Al 2 O 3 is "wetable" for FeO x and will probably cause it to spread into a thin layer [1,2].…”
Section: Comparison Of Routes With Regard To Morphology Feo X /Pt Inmentioning
confidence: 99%
“…This measure is selective for Pt, because CO does not chemisorb on FeOx under the applied conditions, as we determined by a separate set of measurements. By measuring the specific Pt surface areas of comparable samples (i.e., at equal Fe and Pt concentrations) produced by each route, and comparing it to that of a reference sample without any Fe deposit (SPt reference), one can calculate a relative interfacial surface (SInterface), according to Equation (1). It gives the FeOx/Pt area (relative to a reference sample without FeOxSPt reference), for SPt and FeOx denotes the remaining "uncovered" Pt surface of a sample.…”
Section: Comparison Of Routes With Regard To Morphology Feo X /Pt Inmentioning
confidence: 99%
See 1 more Smart Citation